2012
DOI: 10.1016/j.celrep.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the SecY Complex Unlocked by a Preprotein Mimic

Abstract: SummaryThe Sec complex forms the core of a conserved machinery coordinating the passage of proteins across or into biological membranes. The bacterial complex SecYEG interacts with the ATPase SecA or translating ribosomes to translocate secretory and membrane proteins accordingly. A truncated preprotein competes with the physiological full-length substrate and primes the protein-channel complex for transport. We have employed electron cryomicroscopy of two-dimensional crystals to determine the structure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
94
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 38 publications
4
94
0
Order By: Relevance
“…We also did not observe any PpiD cross-linking product when pBpa was incorporated into the N terminus of SecG (Fig. 3), which is located close to helix 3 of the lateral gate (16,46). In summary, these data show that PpiD is positioned in immediate vicinity to the lateral gate of SecY where it contacts all four helices of the lateral gate.…”
Section: The Lack Of Ppid Does Not Significantly Impair In Vitro Proteinmentioning
confidence: 51%
See 1 more Smart Citation
“…We also did not observe any PpiD cross-linking product when pBpa was incorporated into the N terminus of SecG (Fig. 3), which is located close to helix 3 of the lateral gate (16,46). In summary, these data show that PpiD is positioned in immediate vicinity to the lateral gate of SecY where it contacts all four helices of the lateral gate.…”
Section: The Lack Of Ppid Does Not Significantly Impair In Vitro Proteinmentioning
confidence: 51%
“…In conclusion, neither SecA nor ribosome binding to SecY significantly influenced the interaction of PpiD with the lateral gate of SecY. (46) and to allow transmembrane domains to enter the lipid phase of the membrane (52,54). Recent Cryo-EM structures have visualized significant movements at the lateral gate after docking of RNCs onto SecY (52,54).…”
Section: The Lack Of Ppid Does Not Significantly Impair In Vitro Proteinmentioning
confidence: 99%
“…Previous MD simulations (19) and cryo-electron microscopy structures (24,25) suggested that the plug might not completely leave its cavity in the translocon, but only move sideways to accommodate the translocating peptide. Indeed, immobilization of the plug inside bacterial SecYEG did not impair functionality of the translocon (26).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that the channel for transfer of polypeptides lies within a monomer of SecY (1,(15)(16)(17)(18); however, SecYEG exists as monomers, dimers, and higher oligomers (19)(20)(21)(22)(23)(24). Therefore, much controversy has arisen surrounding the question of whether the active translocase comprises a SecYEG monomer or dimer (17,(25)(26)(27)(28).…”
mentioning
confidence: 99%